Green chemistry : an introductory text - Lancaster, Mike (RSC Publishing, 2010)
Annotation The challenge for today's new chemistry graduates is to meet society's demand for new products that have increased benefits, but without detrimental effects on the environment. Green Chemistry: An Introductory Text outlines the basic concepts of the subject in simple language, looking at the role of catalysts and solvents, waste minimisation, feedstocks, green metrics and the design of safer, more efficient, processes. The inclusion of industrially relevant examples throughout demonstrates the importance of green chemistry in many industry sectors.Intended primarily for use by students and lecturers, this book will also appeal to industrial chemists, engineers, managers or anyone wishing to know more about green chemistry.